A start-up in interaction with its partners. Issue 1 (14th March 2016) - Oukes, Tamara; Raesfeld von, Ariane
Abstract : Purpose: – Start-ups are companies that are not yet embedded in a pre-existing network of relationships. Studies that researched how start-ups act in their relationships focused on just one type of action and assumed that start-ups are autonomous in how they choose to act. However, organisational action in relationships is both interactive and dynamic. Therefore, the purpose of this paper is to investigate how a start-up interacts with its partners over time. Design/methodology/approach: – The research aim is addressed through a longitudinal case study of a start-up in the medical device business. It was analysed how this start-up and its six key partners acted and reacted during 18 interactions episodes, what triggered these actions and what the outcomes of their actions were. In addition, the researchers explored if and how the subsequent episodes were related. Findings: – First, the case shows that the past and the future affect current episodes. Second, it shows that action was triggered by both internal and external events which could expand or constrain opportunities for future interactions. Third, the findings show that there was a pattern in the interaction modes used during the relationship. Fourth, the findings show that the initial mode of interaction was often imitated by the counterparty. Finally, it is shown that there are clear links between the trigger, interaction process and outcome in an interaction episode. Research limitations/implications: – The results indicate that besides the focal firm, partners should always be actively and directly involved in any research into organisational action. Moreover, action in relationships should be characterised as a dynamic process that is in a state of continual change. Practical implications: – Managers of start-ups: can influence the outcomes of their relationships through their actions; have to react to both opportunities and conflicts in their relationships; can rely on their network to solve conflicts; and should closely consider their own actions and their counterparty's actions. Originality/value: – The research is valuable because it studies the interactive and dynamic nature of start-ups' action in relationships.